The Colombian situation before the world: interview with Álvaro Uribe Vélez, President of the Republic of Colombia - Cordovez, Diego (2016)
Interview with Alvaro Uribe Vélez, President of the Republic of Colombia, on the issue of the Colombian situation before the world